DETERMINASI SOSIAL DAN ORGANISASIONAL DALAM IMPLEMENTASI PROGRAM KESELAMATAN DAN KESEHATAN KERJA PADA SUBKONTRAKTOR PROYEK INFRASTRUKTUR STRATEGIS: STUDI PADA PEMBANGUNAN BANDARA KOTA X - Yulidta Timory; Intan Pardyani; Cahyo Ari Prastiyo; Novelia Qothrunnada (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The implementation of occupational health and safety (OHS) programs in strategic infrastructure projects is influenced by social and organizational determinants, particularly among subcontractor workers who often experience more vulnerable employment conditions. This study analyzed these determinants among 86 subcontractor workers involved in the construction of an airport in City X. Data were collected using structured questionnaires covering socio-demographic characteristics, employment status, social security participation, exposure to OHS policies, supervision practices, and occupational health program indicators. Most respondents were aged 20–35 years (60.5%) and had secondary education (66.3%); 69.8% were daily or piece-rate contract workers, and 57.0% had worked for less than two years. Social security coverage was reported by 72.1%. Safety induction participation reached 82.6%, and 76.7% reported routine toolbox meetings. Although 79.1% were aware of written OHS policies, only 63.9% reported periodic dissemination. Personal Protective Equipment (PPE) was available for 88.4% of workers, with 73.3% reporting consistent use. Periodic medical examinations were reported by 48.8%, and only 42.0% understood detailed incident reporting procedures. Organizational supervision, structured safety communication, and employment security were associated with stronger implementation of occupational health programs.Keywords: Social Determinants; Organizational Determinants; Occupational Health; Subcontractor Workers; Infrastructure Project Benach, J., Vives, A., Amable, M., Vanroelen, C., Tarafa, G., Muntaner, C. (2014). Precarious employment: Understanding an emerging social determinant of health. Annual Review of Public Health, 35, 229–253.Bloom, H. L., (1974). Planning for Health, Development and Aplication of Social Changes Theory. New York: Huma Sciencess PressInternational Labour Organization. (2019). Safety and health at the heart of the future of work: Building on 100 years of experience. Geneva: ILO.International Labour Organization. (2022). World employment and social outlook: Trends 2022. Geneva: ILO.ISO. (2018). ISO 45001:2018 Occupational health and safety management systems — Requirements with guidance for use. Geneva: International Organization for Standardization.Kines, P., Andersen, L. P. S., Spangenberg, S., Mikkelsen, K. L., Dyreborg, J., Zohar, D. (2010). Improving construction site safety through leader-based verbal safety communication. Journal of Safety Research, 41(5), 399–406.Lingard, H., Rowlinson, S. (2005). Occupational health and safety in construction project management. London: Spon Press.Manu, P., Ankrah, N., Proverbs, D., Suresh, S. (2013). Mitigating the health and safety influence of subcontracting in construction: The approach of main contractors. International Journal of Project Management, 31(7), 1017–1026.Marmot, M., Wilkinson, R. G. (Eds.). (2006). Social determinants of health (2nd ed.). Oxford University Press.Undang-Undang Nomor 1 Tahun 1970 tentang Keselamatan Kerja.Undang-Undang Nomor 36 Tahun 2009 tentang Kesehatan.Peraturan Pemerintah Nomor 50 Tahun 2012 tentang Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja.Quinlan, M., Mayhew, C., Bohle, P. (2001). The global expansion of precarious employment and occupational health: A review of recent research. International Journal of Health Services, 31(2), 335–414.Zohar, D. (2010). Thirty years of safety climate research: Reflections and future directions. Accident Analysis Prevention, 42(5), 1517–1522.